Monomeric and dimeric states of human ZO1-PDZ2 are functional partners of the SARS-CoV-2 E protein - Noah Giacon; Ettore Lo Cascio; Darcy S. Davidson; Marcelo D. Polêto; Justin A. Lemkul; Valeria Pennacchietti; Livia Pagano; Carlotta Zamparelli; Angelo Toto; Alessandro Arcovito (Computational and Structural Biotechnology Journal, 2023)
The Envelope (E) protein of SARS-CoV-2 plays a key role in virus maturation, assembly, and virulence mechanisms. The E protein is characterized by the presence of a PDZ-binding motif (PBM) at its C-terminus that allows it to interact with several PDZ-containing proteins in the intracellular environment. One of the main binding partners of the SARS-CoV-2 E protein is the PDZ2 domain of ZO1, a protein with a crucial role in the formation of epithelial and endothelial tight junctions (TJs). In this work, through a combination of analytical ultracentrifugation analysis and equilibrium and kinetic folding experiments, we show that ZO1-PDZ2 domain is able to fold in a monomeric state, an alternative form to the dimeric conformation that is reported to be functional in the cell for TJs assembly. Importantly, surface plasmon resonance (SPR) data indicate that the PDZ2 monomer is fully functional and capable of binding the C-terminal portion of the E protein of SARS-CoV-2, with a measured affinity in the micromolar range. Moreover, we present a detailed computational analysis of the complex between the C-terminal portion of E protein with ZO1-PDZ2, both in its monomeric conformation (computed as a high confidence AlphaFold2 model) and dimeric conformation (obtained from the Protein Data Bank), by using both polarizable and nonpolarizable simulations. Together, our results indicate both the monomeric and dimeric states of PDZ2 to be functional partners of the E protein, with similar binding mechanisms, and provide mechanistic and structural information about a fundamental interaction required for the replication of SARS-CoV-2.